Tourism development and changes in life satisfaction: Case of Balinese community in Canggu traditional village, North Kuta - Pramudya, Wisnu; Ahimsa-Putra, Heddy Shri; Widiyastuti, Dyah (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
Extensive research on Bali's tourism has explored its development and various impacts, yet there is limited understanding of how tourism specifically affects the life satisfaction of local communities, particularly the Balinese. This study aims to investigate the changes in life satisfaction within the Balinese community of Canggu traditional village, driven by the rapid development of tourism. Adopting a qualitative approach, the research utilized participant observation and semi-structured interviews for data collection. A total of 17 informants were purposively selected to ensure diverse perspectives, enhancing the methodological rigor. Thematic analysis was conducted to identify patterns in how life satisfaction has evolved in response to tourism growth. The findings reveal that tourism has notably influenced various aspects of life satisfaction in Canggu, with significant improvements observed in financial stability. Before tourism, life satisfaction in the community was primarily derived from simple living, a sense of gratitude, strong social bonds, and adherence to traditional values, although financial limitations often led to dissatisfaction. With the expansion of tourism, improved economic conditions have enabled the community to enhance religious rituals, gain better access to education and healthcare, enjoy more leisure activities, and improve the condition of basic needs such as food, clothing, and housing. Moreover, the growth of cultural activities has fostered stronger social interactions, further enriched social relations, and boosted overall community satisfaction. However, to sustain these benefits, balancing tourism development with community welfare is crucial through strategies that promote both economic and cultural sustainability.